Antifouling applications and fabrications of biomimetic micro-structured surfaces: A review - Yuhan Liu; Xiaoyan He; Chengqing Yuan; Pan Cao; Xiuqin Bai (Journal of Advanced Research, 2024)
Background: Since the inception of the term “Biomimetics” in 1991, the concept of utilizing natural solutions or deriving inspiration from nature to address contemporary engineering challenges has gained significant attention within the scientific community. Organisms, in order to thrive in harsh environments, have evolved a wide range of micro/nanostructured surfaces, which serve as a rich source of inspiration for the development of artificial micro/nano-structured surfaces. These natural adaptations provide valuable insights and novel pathways for fabricating such surfaces. Aim: To conclude recent advances in micro/nano-structured surfaces from four aspects: biomimetic micro-structured surfaces of plants and animals, properties and applications of biomimetic surfaces, methods of preparations, and their limitation. Key Scientific Concepts:: Artificial micro/nano-structured surfaces inspired by animals and plants are classified and demonstrated according to their living environment. The performances, principles and preparation techniques of natural superhydrophobic surfaces, slippery liquid-infused porous surfaces (SLIPS), anisotropic surfaces, etc. are described in detail. Moreover, the pros and cons of each preparation measures are compared and the challenges developing large-scale, cost-effective surface microstructure preparation processes are pointed out. In the end, the development trends of artificial micro/nano-structured surface are forecasted.